2019
DOI: 10.1021/acs.nanolett.9b02427
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Cascaded Third-Harmonic Generation in Noncentrosymmetric Gold Nanoantennas

Abstract: The optimization of nonlinear optical processes at the nanoscale is a crucial step for the integration of complex functionalities into compact photonic devices and metasurfaces. In such systems, photon upconversion can be achieved with high efficiencies via third-order processes, such as third harmonic generation (THG), thanks to the resonantly enhanced volume currents. Conversely, second-order processes, such as second harmonic generation (SHG), are often inhibited by the symmetry of metal lattices and of com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Given the remarkably high efficiency attained at the nanoscale, individual plasmonic nanoantennas were recently exploited also for ultrafast pulse characterization [Extermann et al (2008), Accanto et al (2014), Gennaro et al (2018)]. In perspective, the possibility of finely tuning the geometry of plasmonic nanoantennas using modern lithographic techniques would allow one to further enhance nonlinear processes at the nanoscale through cascaded nonlinear processes [Celebrano et al (2019)] and envision their employment also as nanoscale parametric amplifiers [Zhang et al (2016)].…”
Section: Enhanced Harmonic Generation At the Nanoscalementioning
confidence: 99%
“…Given the remarkably high efficiency attained at the nanoscale, individual plasmonic nanoantennas were recently exploited also for ultrafast pulse characterization [Extermann et al (2008), Accanto et al (2014), Gennaro et al (2018)]. In perspective, the possibility of finely tuning the geometry of plasmonic nanoantennas using modern lithographic techniques would allow one to further enhance nonlinear processes at the nanoscale through cascaded nonlinear processes [Celebrano et al (2019)] and envision their employment also as nanoscale parametric amplifiers [Zhang et al (2016)].…”
Section: Enhanced Harmonic Generation At the Nanoscalementioning
confidence: 99%
“…[20] Plasmonic nanoantennas can be used to generate hot electrons [21] or current [22] and find applications in photochemistry, [23] energy harvesting devices, [24] and photon detectors. [25] Field enhancement in the hotspot near nanoparticle surfaces is used to enhance nonlinear effects [26] such as second harmonic, [27,28] third harmonic signal, [29] coherent anti-Stokes Raman scattering, [30] and four-wave mixing. [31] Likewise, if a plasmonic nanoantenna is combined with a gain material and their modes overlap spatially and spectrally, plasmonic lasing can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these signals exerted on micro-and nano-structures have been previously observed individually [6][7][8] or in combinations of two or three of them. [9][10][11][12][13][14][15] Very recently, Liu et al reported the simultaneous emission of harmonics and wave-mixing signals from a 3 µm diameter region of a GaAs-based dielectric metasurface optimized for 1.24 and 1.57 µm excitation using a kHz source. 16 Here, using a dual output laser developed for microscopy and sub-micron particles, we demonstrate a similar multi-order phase-coherent response spanning from fifth harmonic generation (FiHG) of a 1300 nm pulse (260 nm) to four-wave mixing (4WM) leading to emission at 2061 nm.…”
Section: Introductionmentioning
confidence: 99%